Nghiên cứu sản xuất nấm men giàu selen (qui mô phòng thí nghiệm) - Nguyễn, Quang Thường (2011)
Tác giả: Nguyễn Quang Thường, TS; Nguyễn Thị Thơm; Nguyễn Văn Thưởng; Nguyễn Trọng Thông; Phạm Văn Nguyện -- Từ khóa: Nấm men; Nấm men giàu selen